2004
DOI: 10.1177/1523422304266075
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Development as National Policy in India

Abstract: The problem and the solution. Although India took the lead in the Asia Pacific region, setting up a full Ministry of Human Resource Development, the National human resource development concept in India has largely been limited to education and culture. The complexity of the country perhaps makes it difficult to have integrated HRD systems at the national level. Networking and learning from each other among various ministries and institutions and from the corporate sector will, however, go a long way in effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…In contrast to both the macro and meso levels of analysis, papers examining the micro level explored the processes involved in implementing NHRD. These factors generally focused on NHRD-specific actors (Akanji and Bankole, 2007; Alagaraja and Wang 2012 AQ20 ; Heraty and Collings 2006), NHRD-specific implementation bodies (Arthur-Mensah and Alagaraja 2013; Asrar-ul-Haq 2015; Elkin 1998), NHRD actors' perceptions and behaviours (Paprock, Yumol, and Atienza 2006;Rao 2004;Wilkins 2001), and social resources and capital of NHRD actors (Ahn and Mclean 2006;Nry-Kjerfve et al 2014…”
Section: Aq19mentioning
confidence: 99%
“…In contrast to both the macro and meso levels of analysis, papers examining the micro level explored the processes involved in implementing NHRD. These factors generally focused on NHRD-specific actors (Akanji and Bankole, 2007; Alagaraja and Wang 2012 AQ20 ; Heraty and Collings 2006), NHRD-specific implementation bodies (Arthur-Mensah and Alagaraja 2013; Asrar-ul-Haq 2015; Elkin 1998), NHRD actors' perceptions and behaviours (Paprock, Yumol, and Atienza 2006;Rao 2004;Wilkins 2001), and social resources and capital of NHRD actors (Ahn and Mclean 2006;Nry-Kjerfve et al 2014…”
Section: Aq19mentioning
confidence: 99%
“…Its realisation in practice, therefore, will depend much on pre-existing social, political, cultural and historic conditions and on geographical location (Lynham and Cunningham 2006) and it remains up to the people involved in different societies to figure out by democratic deliberation how FITM could and should be implemented, if at all. However, the principles of FITM connect to different national HRD priorities and examples include lifelong learning and workplace transformation in Singapore (Osman-Gani 2004), poverty alleviation in India (Rao 2004) and raising performance in South Africa (Lynham and Cunningham 2004).…”
Section: For National Hrdmentioning
confidence: 99%
“…We begin this section by highlighting NHRD HRD literature investigating the separate case country contexts of India and China. Rao's (2004) review of the NHRD context revealed education and culture as two important factors for policy development. Rao (2004) and Rao and Varghese (2009) also underlined the complex interplay of economic, political and social structures, demographics, as well as diverse and multifaceted characteristics affecting India.…”
Section: Nhrd In India and Chinamentioning
confidence: 99%
“…Rao's (2004) review of the NHRD context revealed education and culture as two important factors for policy development. Rao (2004) and Rao and Varghese (2009) also underlined the complex interplay of economic, political and social structures, demographics, as well as diverse and multifaceted characteristics affecting India. In a similar fashion, Ke et al (2006) explored HRD's contribution toward China's economic, social, cultural, and political growth.…”
Section: Nhrd In India and Chinamentioning
confidence: 99%